A review of the Profile of Mood States (POMS) in the prediction of athletic success - Renger, R. (Journal of Applied Sport Psychology, 1993)
The POMS is used frequently to assess the trained states of athletes. It is often reputed to be able to indicate a) when a stale or overtrained state exists, and b) profiles that differentiate successful and unsuccessful athletes. This article reviewed the efficacy of these propositions and interpretations. The POMS was found to be of limited value in differentiating successful from unsuccessful athletes. Despite this fact, studies continue to be published that examine the POMS' ability to differentiate athletes of differing levels of ability. This misunderstanding is attributed to researchers' failure to distinguish between two common approaches to the study of personality in sport: the identification of personality characteristics that differentiate a) athletes of differing levels of ability, and b) the athlete from non-athlete. Studies which have demonstrated these errors serve as a reminder of the importance of examining original contributions. Many of the problems surrounding the utility of the POMS can be traced to Morgan's (1980) paper [Morgan, W. P. (1980). Test of champions. Psychology Today, 14, 92-108.], published in a popular journal. In writing for the layman, Morgan provided an oversimplified summary of his work with the POMS. Researchers who may have relied on this paper to guide their own work could have been easily misled. There is little to no available evidence to justify the continued use of the POMS to attempt to differentiate levels of athletic ability.